Self Control and Organizational Commitment Views of Cyberloafing Behavior - Masruroh*, Rina; Budiman, Aris; Dodi, Dodi; Komarudin, Munir Nur; Irawan, Nico (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
Internet facilities in the workplace are often misused for personal purposes, known as cyberloafing behavior. This study utilizes multiple linear regression analysis to understand the influence of self-control and organizational commitment on employees' cyberloafing behavior in private companies in Kuningan Regency, both partially and simultaneously, through the distribution of questionnaires as a data collection technique on 100 sampled employees. The results show that organizational commitment does not have a significant impact, while self-control can reduce cyberloafing behavior. These research findings can serve as recommendations for local private business owners to improve their employees' performance by enhancing control over cyberloafing behavior, focusing on self-control aspects, and also increasing employee work commitment. Keywords: Cyberloafing; Self Control; Organizational Commitment; Employee Performace; Privat Employees